Cut-Size Diameter Calculation of Salt Crystals From A Hydrocyclone - Paramitasari, Derina; Sugeng, Dhani Avianto (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
A hydrocyclone is physical separation equipment employed in solid-liquid processing. An important parameter in hydrocyclone design is the so-called cut-size diameter (D50), which determines the minimum size of the separated solids when the equipment performs at 50% separation efficiency. This paper discusses the calculation of the cut-size diameter (D50) of a hydrocyclone operating in a salt purification pilot plant in Manyar, East Java, Indonesia. The cut-size D50 is calculated based on the residence time approach and compared with the collection efficiency from the mass balance. D50 was found to be 69.73 microns. Moreover, by using Zanker’s nomograph, it was found that at the solid separation efficiency of 80.48%, the minimum diameter of salt crystal (Dmin) is 85 microns. Because the D50 of HC-1 is smaller than Zanker’s design, it can be concluded that the hydrocyclone will work efficiently in separating the expected products.